The Philosophy of Maturity and Acmelogy Under Conditions of Socio-Cultural Change in Uzbekistan - Kamalova Khatira (Goodwood Publishing, 2025)
Purpose: This study explores maturity as a personal condition beyond age, linking it to responsibility, self-knowledge, and inner harmony. It examines its evolution through philosophical perspectives and highlights the changing role of older generations in Uzbekistan and Karakalpakstan due to demographic shifts. Research Methodology: Using a qualitative approach, this study analyzes philosophical and sociological literature from classical thinkers and modern scholars, combined with demographic data from Uzbekistan. The research is based on theoretical analysis of existing frameworks related to maturity. Results: The study concludes that maturity is increasingly understood as the peak of human life, a phase of self-realization and spiritual development. The role of the older generation is highlighted, particularly in Uzbekistan and Karakalpakstan, where older adults are seen as carriers of wisdom, experience, and cultural continuity. The study also finds that contemporary society must rethink how it views aging and the contributions of mature individuals, emphasizing the need for a new culture of maturity based on active longevity and intergenerational solidarity. Conclusions: Maturity should be understood a valuable phase that contributes to both individual fulfillment and societal development. Societies, particularly in Uzbekistan, must create environments where mature individuals remain active and involved. Limitations: The study relies on secondary sources, limiting empirical data and direct insights from mature individuals, particularly from rural regions like Karakalpakstan. Contributions: This research provides insights into the role of older generations in modern society and suggests ways to integrate maturity into social policies and cultural programs, especially in the context of Uzbekistan's demographic changes.